ASSESSING THE IMPACTS OF MEGA SPORTING EVENTS ON MIGRANT WORKERS: A CASE OF THE 2022 FIFA WORLD CUP IN QATAR - Khalifa, Nasser K A Al-Dosari (Journal of Philosophy, Culture and Religion, 2020)
Purpose: The purpose of the study was to assess the impacts of mega sporting events on migrant workers, by exploring the skills needs and the challenges faced by migrant workers, and the measures put in place to safeguard migrant workers in relation to the 2022 FIFA World Cup in Qatar. Methodology: The research was a case study based on the 2022 FIFA World Cup in Qatar, through both descriptive and exploratory research designs. Structured questionnaires were administered to the respondents, with a sample size of 61 respondents who were randomly sampled used for data analysis for the study. Random sampling technique was used to ensure respondents from each sample comprising skilled manual workers, service workers, social workers, and managerial/professional workers were given an equal opportunity of being chosen without biased selection and representation of the target population. The quantitative data obtained was analysed using the SPSS version 25 for data analysis through the use of descriptive statistics such as percentages, which were presented using tables and charts. Further, the study variables were analysed using a regression equation. Findings: The findings of the study indicated that there has been an influx of migrant workers since 2010 as a result of Qatar being granted the hosting rights for the FIFA 2022 World Cup. Further, the findings revealed that these migrant workers have encountered challenges while working in Qatar in preparation for the 2022 FIFA World Cup. Moreover, the study found out that migrant workers' welfare had improved as a result of the measures employed by the Qatar government to safeguard their welfare. Unique contribution to theory, policy and practice: The researcher concluded that the skills need for migrant workers, challenges faced by migrant workers and the measures employed by the Qatar government have an impact on the performance of the migrant workers as well as their welfare. Therefore, the researcher recommends a continual increase of efforts in the study objectives to set a high standard to be adopted by other countries intending to hold mega sporting events.